The three worlds of welfare capitalism - Esping-Andersen, Gøsta (Polity Press, 2020)
Few discussions in modern social science have occupied as much attention as the changing nature of the welfare states in Western societies. The author aims to provide an analysis of the character and future of welfare institutions and discusses several types of welfare state, connecting these with variations in the historical development of different Western countries. Current economic processes, the author argues, such as those moving towards a post–industrial order, are not shaped by autonomous market forces but by the nature of states.